PENGARUH KARIR DAN PENGEMBANGAN ORGANSASI TERHADAP KINERJA KARYAWAN STUDI KANTOR SERAMBI INDONESIA CABANG BANDA ACEH - Lailatul Fajar; Mahdani Mahdani (Departemen Manajemen, 2021)
This study aims to determine the effect of career and organizational development on employee performance. The sample consisted of 94 respondents who worked at the Serambi Indonesia branch office in Banda Aceh. The sampling technique uses probability sampling methods. Data collection is done through surveys with questionnaire methods. The data analysis technique used is SPSS is the statistical method chosen to describe the observed variables. The results showed that the career was not significant on employee performance, significant organizational development on employee performance, career influences on employee performance, organizational development influenced employee performance, and career and organizational development simultaneously had a significant effect on employee performance. Keywords: career, organizational development, employee performance.